SULBACTAM/CEFOPERAZONE: ANTIMICROBIAL ACTIVITY AND CLINICAL INVESTIGATION ON RESPIRATORY TRACT INFECTIONS - WATANABE, AKIRA; SASAKI, MASAKO; AONUMA, SEIICHI; ONUMA, KIKUO; OIZUMI, KOTARO; KONNO, KIYOSHI (CHEMOTHERAPY, 1984)
In vitro antimicrobial activity of Sulbactam/Cefoperazone (SBT/CPZ) which has a composition of 1:1 of Cefoperazone (CPZ) and Sulbactam (SBT), a potent inhibitor of many β-lactamases, was examined by a broth dilution method with Dynatech MIC 2000 system. Also, therapeutic efficacy of Sulbactam/Cefoperazone in the treatment of patients with respiratory tract infections was evaluated. The minimum inhibitory concentrations (MICs) of Sulbactam/Cefoperazone were compared with those of Cefoperazone, Cefmetazole (CMZ), Cefazolin (CEZ), Cefsulodin (CFS) and Piperacillin (PIPC) against following 20 strains each of clinical isolates; Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Enterobacter cloacae, Serratia marcescens, Pseudomonas aeruginosa. Reductions in the MICs of Cefoperazone in the presence of Sulbactam were marked for penicillinase-producing strains of Escherichia coil, Klebsiella pneumoniae, Enterbacter cloacae and Pseudomonas aeruginosa, but less extent for cephalosporinase-producing strains of Serratia marcescens. Sulbactam/Cefoperazone was given to a total of 12 patients by an intravenous drip infusion. The subjects examined consisted of four patients each of acute pneumonia, infection associated with bronchiectasis and infection associated with lung cancer. A daily dose of the drug given was 2 grams in 11 patients and 4 grams in one patient. Clinical response to the treatment with the drug was excellent in five patients, good in five patients and poor in two patients. Following eight potential pathogens were recovered from the sputum of these patients at the start of the treatment with the drug; four strains of Haemophilus influenzae, one strain each of Streptococcus pyogenes, Escherichia coli, Klebsiella pneumoniae and Acinetobacter calcoaceticus. All of them, including three strains which has β-lactamase activity, were eradicated during the treatment with the drug. Transient diarrhea was observed in three patients among these 12 patients and in one patient among three patients with diarrhea, transient anemia and eosinophilia was complicated but returned to normal after the cessation of the drug.